Mosaic Diseases of Cucurbits - Botirova Irodea Sayimovna (Genius Publishing Group, 2021)
Many viruses affect grape crops or pumpkin crops and cause mosaic lesions. The most important of these viruses in the Midwest are cucumber mosaic virus (CMV), mosaic pumpkin virus (SqMV), watermelon mosaic virus (WMV), and tobacco ring spot virus (TRSV). Viruses vary in the range of host plants they infect, in the ways they survive between cultures, and in the ways in which they are transmitted. Because management programs are based on this information, it is important to identify the relevant virus or viruses
Keywords: Viruses, mosaicviruses; mosaic cucumber; Symptoms of COI